Glassy cell carcinoma: A rare variant of cervical carcinoma – Case report with review of literature - Nidhi Raina; Anchana Gulati; Rajni Kaushik; Akshay Rana (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2018)
Glassy cell carcinoma is a rare clinical entity involving uterine cervix with aggressive course and relatively poor prognosis. It is a poorly differentiated variant of adenosquamous carcinoma. This neoplasm has poor response to radiotherapy and carries worse prognosis than the usual types of adenocarcinoma and squamous cell carcinoma. A case of a 40-year-old female patient is reported and the published literature is reviewed.